Klinefelter syndrome and fertility—Impact of X‐chromosomal inheritance on spermatogenesis. (7th March 2018) - Franik, S.; Smeets, D.; van de Zande, G.; Gomes, I.; D'Hauwers, K.; Braat, D. D. M.; Fleischer, K.; Ramos, L.
Summary: With the use of testicular sperm extraction (TESE), spermatozoa can be retrieved in about 30%‐50% of men with Klinefelter syndrome (KS). The reason for the absence or presence of spermatozoa in half of the men with KS remains unknown. Therefore, the search for an objective marker for a positive prediction in finding spermatozoa is of significant clinical value to avoid unnecessary testicular biopsies in males with (mostly) low testicular volume and impaired testosterone. The objective of this study was to determine whether paternal or maternal inheritance of the additional X‐chromosome can predict the absence or presence of spermatogenesis in men with KS. Men with KS who have had a testicular biopsy for diagnostic fertility workup TESE were eligible for inclusion. Buccal swabs from nine KS patients and parents (trios) were taken to compare X‐chromosomal inheritance to determine the parental origin of both X‐chromosomes in the males with KS. Spermatozoa were found in TESE biopsies 8 of 35 (23%) patients after performing a unilateral or bilateral TESE. Different levels of spermatogenesis (from the only presence of spermatogonia, up to maturation arrest or hypospermatogenesis) appeared to be present in 19 of 35 (54%) men, meaning that the presence of spermatogenesis not always yields mature spermatozoa. From the nine KS‐trios that were genetically analysed for X‐chromosomal inheritance origin, no evidence of a correlation between the maternal or paternal origin of the additional X‐chromosome and the presence of spermatogenesis was found. In conclusion, the maternal or paternal origin of the additional X‐chromosome in men with KS does not predict the presence or absence of spermatogenesis.